Myxomycete with the ability to accumulate heavy metals. Meriderma echinulatum - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (CABI, 2019)
Diagnostic features. Sporocarps sessile or sometimes short-stalked sporangia; peridium usually fragmented or entirely absent; capillitium with funnel-shaped ends (such funnels absent from Lamproderma), sometimes with small peridial fragments adhering to the funnels; spores en masse black, with irregular ornamentation of long spines.
Keywords: myxomycetes; міксоміцети; Meriderma echinulatum